Neuropeptide PACAP in Mouse Liver Ischemia and Reperfusion Injury: Immunomodulation via cAMP-PKA Pathway - Ji, Haofeng (2013)
Hepatic ischemia and reperfusion injury (IRI), an exogenous antigen-independent local inflammation response, occurs in multiple clinical settings including liver transplantation, hepatic resection, trauma, and shock. The immune system and the nervous system maintain extensive communication, and mount a variety of integrated responses to danger signals through intricate chemical messengers. This study examined the function and potential therapeutic potential of neuropeptide PACAP (pituitary adenylate cyclase-activating polypeptide) in a murine model of partial liver “warm” ischemia (90min) followed by reperfusion. Liver IR readily triggered the expression of intrinsic PACAP and its receptors, whereas the hepatocellular damage was exacerbated in PACAP-deficient mice. Conversely, PACAP27, or PACAP38 peptide monotherapy, which elevates intracellular cyclic adenosine monophosphate - protein kinase A (cAMP-PKA) signaling, protected livers from IRI, as evidenced by diminished serum alanine aminotransferase (sALT) levels and well-preserved tissue architecture. The liver protection rendered by PACAP peptides was accompanied by diminished neutrophil/macrophage infiltration and activation, reduced hepatocyte necrosis/apoptosis, and selectively augmented hepatic IL-10 expression. Strikingly, PKA inhibition readily restored liver damage in otherwise IR-resistant PACAP-conditioned mice. In vitro, PACAP treatment not only diminished macrophage TNF-α/IL-6/IL-12 levels in an PKA-dependent manner, but also prevented necrosis and apoptosis in primary mouse hepatocyte cultures. CONCLUSION: Our novel findings document the importance of PACAP mediated cAMP-PKA signaling in hepatic homeostasis and cytoprotection in vivo. As the enhancement of neural modulation differentially regulates local inflammation and prevents hepatocyte death, these results provide the rationale for novel approaches to manage liver inflammation and IRI in transplant patients.